‘Azl al-Hakim Baina al-Fiqh wa al-Qanun: Dirasah Muqaranah bi al-Qanun al-Yamani - al-Ansi, Abdel Salam Hammoud Ghaleb (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2023)
It is noticeable in the life of the Islamic nation and by tracing the biography of the Messenger and the Rightly Guided Caliphs after him, how was the interest in appointing the ruler and the concern for the presence of a ruler for the nation who applies the Sharia and establishes borders between people and protects the egg of Muslims, and the Messenger had sent deputies to him in places far from him, like sending Moaz to Yemen May you live among them, because of the importance of this subject in Islamic legislation and Islam’s keenness to secure people’s lives and their property, because when the ruler is absent, corruption and domination of the powerful appear, rights are lost and strife prevails, and due to the importance of the subject, we note the Islamic legislation setting controls and conditions for this ruler, and specifying when he is dismissed, and we mention here in this tagged research B (Isolation of the ruler between jurisprudence and law, a comparative study with Yemeni law) A summary of what is related to the removal of the ruler in Islamic jurisprudence with a comparison to the republican and royal systems, as we will show, and I chose the comparison with Yemeni and Egyptian law as a model for the republican system, and Saudi Arabia as a model for the monarchy